An Evaluation of Physical Access Barriers to COVID-19 Vaccines Uptake among Persons with Physical Disabilities in Western Kenya - Odongo, David Omondi; Osir, Esther; Awandu, Shehu Shagari (An Evaluation of Physical Access Barriers to COVID-19 Vaccines Uptake among Persons with Physical Disabilities in Western Kenya, 2024)
Physically disabled persons continue to be discriminated, excluded and neglected based on design of structures and their location. This hampers equitable access to services and disproportionately affect them during a pandemic. This study aimed to evaluate physical access barriers to COVID-19 vaccines among persons with physical disabilities during the COVID-19 pandemic, (March 2020 to March 2022) in Ugenya Sub-county, Siaya County in Western Kenya. Methods The study design was cross-sectional. 108 physically disabled participants were selected using systematic sampling technique. Data was collected using structured questionnaires. Results Vaccination location (χ2=95.480, p=0.001), access to the vaccination room (χ2=84.098, p=0.001) and mobility impaired (χ2 = 16.168, p=0.001) had statistically significant associations with uptake of COVID-19 vaccine. Income levels, belief in existence of COVID-19, information from mass media and being married increased the odds of becoming vaccinated (AOR=1.5, 95% CI 0.7–3.4), (AOR=1.8, 95% CI 0.8-4.0) (AOR=2.5, 95% CI 1.5–4.2) and (AOR=2.2, 95% CI 1.3–3.9) respectively. The binary logistic regression analysis showed that transport cost and age (p=0.001) had statistically significant associations with COVID-19 vaccine access and uptake. Those who had difficulty in movement and speaking found uptake of COVID-19 vaccine hard (p=0.001). Conclusion Marital status, information from reliable sources, belief in existence of COVID-19 were associated with access to and uptake of COVID-19 vaccine. Additionally, nonpayment of transport cost increased the odds of becoming vaccinated. Therefore, mobile health teams should be put in place to reach the physically disabled who are hard-to-leave home. Additionally, reimbursement of amount spent on transportation can be adopted to boost access to healthcare services by the physically disabled persons.
Keywords: COVID-19; Access; Physical Disabilities; Physical Barriers